Age Invaders: Inter-generational Mixed Reality Family Game - Khoo, E.T.; Cheok, A.D. (International Journal of Virtual Reality, 2006)
This paper introduces Age Invaders (AI), a novel interactive inter-generation social-physical game which allows the elderly to play harmoniously together with children in physical space while parents can participate in the game play in real time remotely through the internet